2007
DOI: 10.1111/j.1469-8749.2007.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Goal attainment scaling in paediatric rehabilitation: a critical review of the literature

Abstract: The aim of the study was to review the psychometric properties and use of goal attainment scaling (GAS) in paediatric rehabilitation research. We performed a critical literature review searching: (1) all studies whose main focus was to assess the psychometric properties of GAS in paediatric rehabilitation; and (2) all effect studies in paediatric rehabilitation that used GAS as one of the outcome measures. Three articles in the first group and six in the second group met the inclusion criteria. None of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
149
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(157 citation statements)
references
References 30 publications
4
149
0
4
Order By: Relevance
“…To date, this approach has predominantly been confined to adult rehabilitation, 57 although its use in paediatrics has been critically evaluated. 58 This latter piece of work called for more research into the reliability of goal attainment scaling within the paediatric context. A useful piece of work going forward would be to review evidence on this.…”
Section: Participation As An Outcome Measurementioning
confidence: 99%
“…To date, this approach has predominantly been confined to adult rehabilitation, 57 although its use in paediatrics has been critically evaluated. 58 This latter piece of work called for more research into the reliability of goal attainment scaling within the paediatric context. A useful piece of work going forward would be to review evidence on this.…”
Section: Participation As An Outcome Measurementioning
confidence: 99%
“…30 The Melbourne aims to assess the quality of upper limb movements in children with neurological impairment in the age range of 5 to 15 years. The modified Melbourne Assessment of Unilateral Upper Limb Function 31 for children in the age range of 2 to 5 years has recently been developed.…”
Section: Outcome Assessmentsmentioning
confidence: 99%
“…Similar to these studies Steenbeek et al, 2007), we found that GAS was responsive and sensitive to incremental change amongst children. It is difficult to compare our study with previous research in relation to the combination of the model of intervention we used and our primary outcome measure.…”
Section: Discussionsupporting
confidence: 75%
“…There is evidence supporting the use of GAS in the paediatric rehabilitation setting (Steenbeek et al, 2007).…”
Section: Introductionmentioning
confidence: 99%